IoT-Enabled Demand Response and Energy Management System for Smart Homes : Development and Performance Analysis - A’in Sarah, Aidell; Nazreen, Junaidi; Kuryati, Kipli; Sharifah Masniah, Wan Masra; Asrani, Lit (2024)
This research explores the integration of demand response and energy management systems in smart homes, leveraging IoT technologies and AI algorithms to enhance energy efficiency and grid stability. The developed prototype demonstrates the successful incorporation of smart plugs and smart meters to monitor and control energy consumption in real time. The integration with the Smart Life app provided a user-friendly interface for remote control and automation of devices. The system showed significant potential for reducing energy costs and contributing to grid stability during peak demand periods, highlighting the feasibility of smart home technologies in modern energy management.